Correction: Matyushkov et al. Chemical Structure of Lean and Stoichiometric Laminar Flames of Methylcyclohexane at Atmospheric Pressure. Energies 2024, 17, 6154 - Vladislav V. Matyushkov; Anatoly A. Chernov; Artëm M. Dmitriev; Andrey G. Shmakov (Energies)
In the originally published paper [...]